Adherence to Antiretroviral Therapy and Its Related Factors among HIV-Infected Patients: A Mixed-Methods Study - Amin Ghanbari; Maryam Ordibeheshti Khiaban; Nazila Sattari; Azita Fathnezhad Kazemi (Mashhad University of Medical Sciences, 2024)
Background & aim: High levels of adherence to treatment among HIV patients as one of the sexually transmitted diseases (STD) are essential for promoting viral suppression and preventing drug resistance, but little is known about the factors that contribute to antiretroviral adherence. This study aimed to evaluate adherence to therapy and its related factors among HIV-infected patients.Methods: This mixed-methods study was carried out at the Behavioural Diseases Center in Tabriz, Iran in 2021. In a cross-sectional study phase, 137 HIV-infected patients were selected through census sampling method. Then, 21 in-depth interviews were conducted during the qualitative phase using a content analysis approach. Quantitative and qualitative data analysis was performed by SPSS (version 24) and MAXQDA (Version 10), respectively.  Results: The mean score of Adherence was 8.96±2.36 and the majority of participants had moderate to high adherence to treatment. The analyses of regression, predictors of adherence included marital status (β= 0.219, SE= 0.090, P=0.016), income level (β= 0.206, SE= 0.201, P=0.030), and education (β= 0.226, SE= 0.063, P=0.021). Also, two themes of "perceived barriers" and "perceived facilitators" emerged which included six main categories at the individual, socio-environmental and organizational as well as drug and treatment levels.Conclusion: Despite moderate to high adherence, antiretroviral treatment is a challenging issue. Based on the results, various factors play a role as obstacles and facilitators factors of adherence to treatment among HIV patients. So, intervention programs can be aimed at removing barriers and strengthening facilitators based on based on the factors involved.